Structural complexity of defective-interfering RNAs of Semliki Forest virus as revealed by analysis of complementary DNA. - Söderlund, H (1981)
The 18S defective interfering RNA of Semliki Forest virus has been reverse transcribed to cDNA, which was shown to be heterogeneous by restriction enzyme analysis. After transformation to E.coli, using pBR322 as a vector, two clones, pKTH301 and pKTH309 with inserts of 1.7 kb and 2 kb, were characterized, respectively. The restriction maps of the two clones were different but suggested that both contained repeating units. At the 3' terminus, pKTH301 had preserved 106 nucleotides and pKTH309 102 nucleotides from the 3' end of the viral 42S genome. The conserved 3' terminal sequence was joined to a different sequence in the two clones, and these sequences were not derived from the region coding for the viral structural proteins. The DI RNAs represented by the two clones are generated from the viral 42S RNA by several noncontinuous internal deletions, since the largest colinear regions with 42S RNA are 320 nucleotides in pKTH301, and 430 and 340 nucleotides in pKTH309. All these fragments had unique RNase T1 oligonucleotide fingerprints, suggesting that they were derived from different regions of 42S RNA.